Structure and function of the fecal-associated microbiome in qi stagnation constitution - Lu Zhao; Pengfei Zhao; Jianhua Zhen; Guangrui Huang; Yini Li; Anlong Xu (Journal of Traditional Chinese Medical Sciences, 2021)
Objective: To clarify the structural and functional characteristics of the gut microbiota in individuals with qi stagnation constitution (QSC) and identify the potential biomarkers related to QSC. Methods: This cross-sectional study involved individuals with QSC and balanced constitution (BC) confirmed by TCM clinicians. The clinical features were recorded, and fecal samples were collected for 16S rDNA sequencing. The structure of the fecal-associated microbiome (FAM) was described by the alpha-diversity indexes, beta-distances, and relative abundances of dominant taxa. The differences in FAM distribution were analyzed by the Wilcoxon rank-sum test, MetagenomeSeq, and LEfSe analysis. The 16S rDNA gene sequences were assigned to the KEGG dataset to predict the functional information of bacterial metabolic pathways by using PICRUSt. Differences in functional pathways between groups were assessed with the Wilcoxon rank-sum test. The ROC curve based on specific operational taxonomic units (OTUs) was constructed, and the AUC was calculated. Results: Twenty-two individuals with BC and 8 with QSC were recruited. Significant differences between the two groups were found in body mass index, health status, and low-density lipoprotein, etc. There was no significant difference in the alpha-diversity index. PCoA showed no evident clustering of bacterial communities according to constitutions. Bacteroidaceae, Lachnospiraceae, Ruminococcaceae, and Prevotellaceae were the four common bacteria with high abundances. Notably, MetagenomeSeq, LEfSe analysis, and the Wilcoxon rank-sum test identified significantly different distributions of 66, 42, and 36 OTUs, respectively. Predictive function analysis showed that 13 metabolic pathways were significantly differentially distributed, including those related to fatty acid synthesis. Five specific OTUs were selected as potential biomarkers of a QSC, and the AUC was 0.94. Conclusion: Individuals with QSC have unique FAM structure and related functional characteristics. Five specific OTUs were identified to serve as potentially effective biomarkers related to QSC.